Building Christian Leadership According to the Book of Esther Based on Mordecai's Inspirational Mentor Model in Esther - Setiawan, Agus; Abraham, Jovita Elizabeth (IAKN TORAJA, 2024)
Abstract: The implementation of secular leadership values ​​in church ministry can give rise to various problems that impact its integrity and effectiveness. The tendency to pursue quantitative growth and financial success as primary indicators of success can shift the focus away from essential Christian values. In addition, leadership that is not rooted in Christian principles can cause conflict and division within the church body. This research aims to explore the dynamics of Christian leadership that radiate from the story of Mordecai and Esther. This research uses the library research method by analyzing sources relevant to the topics of mentoring, Christian leadership, and the story of Mordecai and Esther. Data were analyzed qualitatively with a focus on Mordecai's role as a mentor, Esther's leadership, and the implications for contemporary Christian leadership. This research produces a 5P mentoring model, based on Mordecai's mentor role to Esther through five main aspects: adoption, care, protection, enlightenment, and strengthening. This is proven to form Esther's leadership character who is brave, wise, faithful and obedient. It is hoped that the findings of this research will help build a Christian leadership model that is effective and relevant to various organizational and community contexts today. Keywords: Esther, Leadership, Mentor, Mordecai